Modern Featuresetiopathogenesis and Clinic of Purulent-Inflammatory Diseases of the Maxillofacial Region - Suleymanova, Tasheva Gulchehra (European Journal of Life Safety and Stability (2660-9630), 2021)
In purulent surgery, a new clinical situation is being formed, associated with an increase in the number of sluggish purulent-inflammatory diseases. The review analyzes the causes of atypical course and chronicity of purulent-inflammatory diseases of the maxillofacial region.